The impact and efficiency of public administration excellence on fostering SMEs in EU countries - Aleksander Aristovnik; Alka Obadić (Amfiteatru Economic Journal, 2015)
The article investigates the impact and efficiency of bureaucracy on the development of small and medium-sized enterprises (SMEs) in the European Union (EU). For this purpose, the article applies a non-parametric approach, i.e. data envelopment analysis (DEA), to assess the best performers in terms of transforming existing bureaucratic burdens into selected SME indicators, such as growth in their numbers, employment or value added in the 2010-2014 period. The empirical results show that Luxembourg, Sweden and, in particular, the Baltic States can serve as a good benchmark for transforming a relatively favourable environment of public administration excellence into SME indicator growth. On the other hand, Denmark and the UK, despite their top ease-of-doing-business rankings could not significantly spur SME growth in the considered period. Nevertheless, the main goal for the large majority of EU member states, especially in South-east Europe and the Mediterranean region, remains a further reduction of bureaucracy that could be useful for improving the regulatory environment of SMEs and thus aid in an even more rapid recovery from the crisis.
Keywords: C14; H83; M10; 330; public administration; small and medium enterprises (SMEs); doing business; efficiency; DEA; EU